Phytochemical Evaluation of Different Plant Sources of Vaasa (Adhatoda Species) - Tomy, Teenu; Ansary, P Y; Oommen, Sara Moncy; Shincymol, V V (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Vaasa, a valuable medicinal plant widely used in Ayurvedic medicine, has experienced growing demand, resulting in the availability of both wild and cultivated sources. Experts have identified morphotypes of Adhatoda species in Kerala, indicating variations in active constituents and clinical efficacy. This study specifically focused on assessing physicochemical parameters and phytochemical constituents of different sources of Vaasa. Materials and Methods: The parameters such as foreign matter, total ash, acid insoluble ash, water insoluble ash, moisture content, volatile oil content, fiber content, tannin content, sugar content, phenol content, pH, qualitative analysis of ash, extractive values, alkaloids, saponins, flavonoids, tannins, steroids, phenols, carbohydrates, and proteins were estimated in different sources of Vaasa (Adhatoda species): A1 (Valiya adalodakam), A2 (Cheriya adalodakam), A3 (Adhatoda species - Vasika), A4 (Adhatoda species - Ajagandhi), and A5 (Adhatoda beddomei C B Clarke). Results and Discussion: The results revealed comparable physicochemical parameters between sample A1 and Adhatoda vasica Nees, as well as between sample A5 and Adhatoda beddomei C B Clarke, as documented in authentic texts and research articles. In qualitative analysis, no differences were found between samples A2, A3, A4, and A5 compared to sample A1. The study revealed quantitative differences in physicochemical and phytochemical evaluation among the powdered leaf samples. Conclusion: Qualitative analysis did not reveal significant differences among samples A2, A3, A4, and A5 compared to sample A1. However, quantitative variations were observed in both physicochemical and preliminary phytochemical evaluation of the powdered leaf sample. The findings in this study contribute to a better understanding and identification of various Vaasa sources in Ayurvedic medicine, essential for quality control and further research.